Sport and Physical Activity in the Heat Maximizing Performance and Safety (Springer International Publishing, 2018)
This unique book is the first of its kind to specifically explore the science, medicine, challenges and successful experiences of assisting those who must perform and thrive in hot conditions, with an eye toward maximizing both performance and safety. Beginning with both human and comparative physiology as it relates to coping with the heat, key concepts are subsequently elaborated, including heat acclimatization, work-to-rest ratios, hydration, sleep, the effects of altitude, and the use of drugs and supplements. The sections that follow discuss heat-related considerations in individual and team sports and other populations, monitoring techniques, and medical and legal issues. Athletes, warfighters and laborers are often forced to perform intense physical activity in the heat as a part of their jobs or lifestyle. The process of properly preparing for this challenge is multifaceted and often not fully understood or utilized. Sport and Physical Activity in the Heat is an excellent resource for team physicians, high-level coaches, serious athletes, athletic trainers, exercise scientists, strength and conditioning coaches, industrial hygienists, military commanders, or anyone involved in the process of maximizing performance and safety during exercise in the heat for the athlete, warfighter, or laborer.